Bifunctional electron transporting layer/perovskite interface linker for highly efficient perovskite solar cells. (10th February 2019) - Han, Fei; Hao, Guimin; Wan, Zhongquan; Luo, Junsheng; Xia, Jianxing; Jia, Chunyang
Abstract: The electron transporting layer/perovskite interface is crucial to the power conversion efficiency of perovskite solar cell. In this work, we study the effect of bifunctional 4-picolinic acid self-assembled monolayer as electron transporting layer/perovskite interface linker on perovskite crystallinity and electron transporting layer/perovskite interface transfer property for high performance perovskite solar cell. Our result shows that the 4-picolinic acid self-assembled monolayer modified device exhibits the highest efficiency of 18.90% and negligible hysteresis index of 0.03 under illumination of AM 1.5G (100 mW cm −2 ), compared to that (14.65%) of the unmodified device. It can be concluded that the bifunctional self-assembled monolayer can be grappled with the TiO2, increase grain sizes of MAPbI3, effectively passivate TiO2 /perovskite interface, and preferably balance electrons and holes transfer, which significantly improves device performance with negligible hysteresis. Our results also indicate bifunctional self-assembled monolayer is a preferable pathway for fabricating high performance and low hysteresis perovskite solar cells. Graphical abstract: Image 1 Highlights: Bifunctional 4-picolinic acid interface linker was studied. The 4-picolinic acid optimizing device exhibits the highest PCE of 18.90%. The 4-picolinic acid optimized PSC exhibits negligible hysteresis. Bifunctional interface linker is a preferable pathway for highly efficient PSCs.